2017
DOI: 10.1108/jsbed-02-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing microfinance

Abstract: Purpose The purpose of this paper is to address the problem of why the poorest, most disadvantaged groups such as rural African women, benefit less from microfinance. The authors focus on the perception and experiences of ordinary rural entrepreneurial women on microfinance in a context of extreme poverty and where family responsibility and economic activities are closely intertwined. Design/methodology/approach The authors purposefully sampled 15 poor females with small businesses in two Nigerian villages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Our selection criteria were based around these being 'interesting' cases. By interesting, we mean that they seemed potentially theoretically rich, offering useful examples of the phenomena; a theoretical sample [53].…”
Section: Methodsmentioning
confidence: 99%
“…Our selection criteria were based around these being 'interesting' cases. By interesting, we mean that they seemed potentially theoretically rich, offering useful examples of the phenomena; a theoretical sample [53].…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, themes surface within context (Anderson and Jack, 2015), but must be recognised by the researcher. Ukanwa et al (2017) explain how identified themes, the patterns of similarity, may then be conceptually linked to form explanations. Iterations between data and data, data and theory are essentially trial and error, a craft rather than science and very dependent on the researcher's inductive skills.…”
Section: Methodsmentioning
confidence: 99%
“…Universally, owners or managers are decision-makers of their businesses and have a critical stake in purchasing, allocating, and using their scarce resources. To make judicious use of these resources that will lead to better financial outcomes, it is agreed among scholars in the MSME sector that every business owner or manager should be financially literate, suggesting the capacity to understand, assess, write and communicate about the financial situation of their enterprises (Ukanwa et al, 2018;Uddin et al, 2017).…”
Section: Relationship Between Financial Literacy and Financial Perfor...mentioning
confidence: 99%